Sensing Properties of NH2-MIL-101 Series for Specific Amino Acids via Turn-On Fluorescence - Jing Dong; Xiao-Yao Dao; Xiao-Yu Zhang; Xiu-Du Zhang; Wei-Yin Sun (Molecules, 2021)
Metal–organic frameworks (MOFs) have been demonstrated to be desired candidates for sensing definite species owing to their tunable composition, framework structure and functionality. In this work, the NH2-MIL-101 series was utilized for sensing specific amino acids. The results show that cysteine (Cys) can significantly enhance the fluorescence emission of NH2-MIL-101-Fe suspended in water, while NH2-MIL-101-Al exhibits the ability to sense lysine (Lys), arginine (Arg) and histidine (His) in aqueous media via turn-on fluorescence emission. Titration experiments ensure that NH2-MIL-101-Fe and NH2-MIL-101-Al can selectively and quantitatively detect these amino acids. The sensing mechanism was examined and discussed. The results of this study show that the metal centers in MOFs are crucial for sensing specific amino acids.